A Study of Transformational Leadership in Bhutto’s Reconciliation: Islam, Democracy and the West - Naheed P Malbari; Javaid Laghari (JISR Management and Social Sciences & Economics, 2010)
This paper is a qualitative study on Benazir Bhutto‟s “Reconciliation” and whether she can be assessed by her book as a transformational leader. Due to a dearth of formal leadership study of Eastern Muslim political leaders as well as their writings, this paper analyzes one such popular democratic leader. As transformational leadership has been of particular importance toresearchers in recent years, this study has used Bass‟s analysis of Parameshwar‟s 2006 study as a premise of the paper. Four aspects of transformational leadership namely as leaders developing „transcendental higher purposes and went beyond the ordinary by 1) exposing unresolved, disturbing human rights problems, 2) untangling false interpretations of the world; 3) breaking out of conventional solutions; and 4) making use of transcendental metaphors, have been used. The construct of Bhutto, challenging prevailing norms and notions of democracy, democratization and extremism in existence both within the Muslim world and the West has been reviewed keeping in mind the leadership premise.